Evaluation Of Passenger Services In White Water Flight Port, Bengkalis District, Riau Province - Slamet Prasetyo Sutrisno; Damaida Hatina; Adelia Adelia (IWJ : Inland Waterways Journal, 2021)
Based on their activities, ports in Riau Province have goals and objectives for improving freight and passenger services. The existence of these Riau ports has an impact on improving Indonesia's economy. Therefore, ferry transportation is important in the Riau Province because it connects with the surrounding area and also to help economic development which of course requires facilities and infrastructure to support the smooth running of people's daily activities. The Air Putih Ferry Port in Bengkalis Regency, Riau Province, serves the Air Putih - Sei Selari route. For this reason, it is necessary to provide services in accordance with statutory regulations in order to carry out good port activities. However, in fact there are still several indicators of service to passengers that are not in accordance with the provisions. Based on these conditions, the authors conducted a literature study on the problems found at the port. Then an analysis is carried out using a method in order to obtain the results of the analysis as well as the problem solving suggestions. The method used to analyze the existing problems is the calculation of the level of conformity of passenger service standards with existing conditions. This method is carried out with the support of surveys related to services to passengers at the port. After that the results of this method will be analyzed with the level of conformity with the Minister of Transportation Regulation No. 39 of 2015. After that obtained the results of the analysis along with the suggestions for solving the problem. Based on the analysis, it can be concluded that there are still services and facilities that are still lacking at the White Water Crossing Port. The percentage of the appropriate aspects is 33.33% while the remaining 66.66% is not suitable.